SYNTHESIS OF CHARACTER BUILDING MODELS THROUGH ISLAMIC RELIGIOUS EDUCATION CURRICULUM: A SYSTEMATIC LITERATURE REVIEW - Erihadiana, Mohammad; Rizky Ramadhani, Annanda Muhamad; Hasilah, Fauzah Nurul; Aulia, Nabila Putri (The Pontianak State Institute of Islamic Studies, 2025)
This Systematic Literature Review (SLR) investigates PAI curriculum alignment with national character development goals. PAI implementation struggles to adapt to 21st-century digital competence demands, forming the main gap. Utilizing an SLR protocol, articles (2020–2025) were analyzed to synthesize curriculum dynamics and relevance gaps. Findings confirm a critical disjunction between PAI’s spiritual objectives and digital skills necessity. The primary contribution is the Synthesis of a novel Character Building Model, integrating PAI values with competence-based learning frameworks, offering practical guidance for policymakers and educators.